2009
DOI: 10.1097/jto.0b013e3181a4ec14
|View full text |Cite
|
Sign up to set email alerts
|

Final Overall Results of a Study with a Novel Triplet Induction Chemotherapy Regimen (PACCAGE) Followed by Consolidation Radiotherapy in Locally Advanced Inoperable Non-small Cell Lung Cancer (NSCLC)

Abstract: Induction chemotherapy with the paclitaxel, carboplatin, and gemcitabine regimen preceding radiotherapy in patients with locally advanced inoperable stage III non-small cell lung cancer was feasible and active. Radiotherapy could be administered at a full dose in the majority of patients with acceptable toxicity. Long-term survival results of this sequential chemoradiotherapy regimen appear similar to those of concurrent treatment. Patients not achieving a metabolic complete response after induction chemothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…In the study by Schallier et al ., with 64 patients constituting the study population, 55% PR was obtained after three cycles of triplet induction chemotherapy regimen of paclitaxel, carboplatin and gemcitabine (PACCAGE). 19 In the study by Hirsh et al . of 41 assessable patients who were treated with induction two cycles of carboplatin and gemcitabine 73.1% achieved PR and 24.4% SD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study by Schallier et al ., with 64 patients constituting the study population, 55% PR was obtained after three cycles of triplet induction chemotherapy regimen of paclitaxel, carboplatin and gemcitabine (PACCAGE). 19 In the study by Hirsh et al . of 41 assessable patients who were treated with induction two cycles of carboplatin and gemcitabine 73.1% achieved PR and 24.4% SD.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there were several attempts to improve results of treatment locally advanced NSCLC. Trials with concurrent radiochemotherapy in combination with induction or consolidation chemotherapy using platinum-based combinations report median survival in the range of 13 to 29.5 months 19 23 , 26 29 , 3-year survival in the range of 13% to 39.8% 22 , 27 and 5-year survival in the range of 12.5% to 22%. 19 , 26 , 29 …”
Section: Discussionmentioning
confidence: 99%
“…Only one patient in arm B (1.9%) had progressive disease. In the study by Schallier et al ., with 64 patients constituting the study population, 55% PR was obtained after three cycles of triplet induction chemotherapy regimen of paclitaxel, carboplatin and gemcitabine (PACCAGE) 19. In the study by Hirsh et al .…”
Section: Discussionmentioning
confidence: 99%
“…Trials with concurrent radiochemotherapy in combination with induction or consolidation chemotherapy using platinum-based combinations report median survival in the range of 13 to 29.5 months1923,2629, 3-year survival in the range of 13% to 39.8%22,27 and 5-year survival in the range of 12.5% to 22% 19,26,29…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it can avoid the morbidity of fruitless CCRT for patients with poor tumor biology who underwent disease progression after induction chemotherapy. [ 22 24 ] With the mechanisms above, patients of locally advanced NSCLC could obtain better long-term survival in induction chemotherapy group than those who only treated by CCRT only. Marquez-Medina et al [ 25 ] reported that for patients treated by induction chemotherapy, the lower presence of angiolymphatic invasion and tumor necrosis were associated with a good survival.…”
Section: Discussionmentioning
confidence: 99%